Cover Feature: Photoluminescent Properties and Mechanism of Novel Cyanine‐Borondifluoride Curcuminoid Hybrids as Red‐to‐Near Infrared and Endoplasmic Reticulum‐Targeting Dyes (Chem. Eur. J. 24/2023). Issue 24 (4th April 2023) - Gong, Shan‐Shan; Chen, Li‐Li; Du, Ke; Yin, Yuwen; Yang, Rui‐Xue; Shi, Rongwei; Peterson, Blake R.; Feng, Fude; Sun, Qi
Abstract : Novel red‐to‐NIR fluorophores called Nanchang Red (NCR) dyes have been constructed by rational structural hybridization of cyanine and borondifluoride curcuminoid. The peculiar asymmetrical layout of the three key fragments endows these long‐wavelength dyes with ideal photophysical properties and ER self‐targeting capability. The photoluminescent mechanism, revealed by quantum chemical calculations, will greatly facilitate future exploration of cyanine‐BF2 hybridized NIR dyes. More information can be found in the Research Article by B. R. Peterson, F. Feng, Q. Sun, and co‐workers (DOI: 10.1002/chem.202300315 ).